Genome-Wide Association Study of Cell-Mediated Response in Dogs Naturally Infected by Leishmania infantum - Batista, Luis F. S.; Utsunomiya, Yuri T. [UNESP]; Silva, Thais B. F.; Dias, Raissa A.; Tomokane, Thaise Y.; Pacheco, Acacio D. [UNESP]; Matta, Vania L. R. da; Silveira, Fernando T.; Marcondes, Mary [UNESP]; Nunes, Caris M. [UNESP]; Laurenti, Marcia D. (Amer Soc Microbiology, 2016)
A genome-wide association study (GWAS) could unravel the complexity of the cell-mediated immunity (CMI) to canine leishmaniasis (CanL). Therefore, we scanned 110,165 single-nucleotide polymorphisms (SNPs), aiming to identify chromosomal regions associated with the leishmanin skin test (LST), lymphocyte proliferation assay (LPA), and cytokine responses to further understand the role played by CMI in the outcome of natural Leishmania infantum infection in 189 dogs. Based on LST and LPA, four CMI profiles were identified (LST-/LPA(-), LST+ /LPA(-), LST- /LPA(+), and LST+ /LPA(+)), which were not associated with subclinically infected or diseased dogs. LST+/LPA(+) dogs showed increased interferon gamma (IFN-gamma) and tumor necrosis factor alpha (TNF-alpha) levels and mild parasitism in the lymph nodes, whereas LST-/ LPA(+) dogs, in spite of increased IFN-beta, also showed increased interleukin-10 (IL-10) and transforming growth factor beta (TGF-beta) levels and the highest parasite load in lymph nodes. Low T cell proliferation under low parasite load suggested that L. infantum was not able to induce effective CMI in the early stage of infection. Altogether, genetic markers explained 87%, 16%, 15%, 11%, 0%, and 0% of phenotypic variance in TNF-alpha, TGF-beta, LST, IL-10, IFN-gamma, and LPA, respectively. GWAS showed that regions associated with TNF-alpha include the following genes: IL12RB1, JAK3, CCRL2, CCR2, CCR3, and CXCR6, involved in cytokine and chemokine signaling; regions associated with LST, including COMMD5 and SHARPIN, involved in regulation of NF-kappa B signaling; and regions associated with IL-10, including LTBP1 and RASGRP3, involved in T regulatory lymphocytes differentiation. These findings pinpoint chromosomic regions related to the cell-mediated response that potentially affect the clinical complexity and the parasite replication in canine L. infantum infection.